2016
DOI: 10.1016/j.rse.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Mapping methane concentrations from a controlled release experiment using the next generation airborne visible/infrared imaging spectrometer (AVIRIS-NG)

Abstract: Emissions estimates of anthropogenic methane (CH4) sources are highly uncertain and many sources related to energy production are localized yet difficult to quantify.Airborne imaging spectrometers like the next generation Airborne Visible/Infrared Imaging Spectrometer (AVIRIS-NG) are well suited for locating CH4 point sources due to their ability to map concentrations over large regions with the high spatial resolution necessary to resolve localized emissions. AVIRIS-NG was deployed during a field campaign to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 34 publications
1
83
0
Order By: Relevance
“…Prior studies of CH 4 with the "Classic" AVIRIS instrument by Thorpe et al (2014) detected local enhancements of 1 ppm within a kilometer-thick atmospheric model layer. Later studies by Thorpe et al (2015) using AVIRIS-NG found similar enhancements in the distal regions of plumes associated with CH 4 fluxes of 14.2 m 3 h −1 (500 standard cubic feet per hour, scfh) under moderate (5 m s −1 ) winds. Resolving plumes of this magnitude under similar conditions should be possible with a sensitivity of 1000 ppm m. Better performance would further reduce ambiguity and improve the detail of diffuse plumes.…”
Section: Tactical Imaging Spectroscopymentioning
confidence: 76%
“…Prior studies of CH 4 with the "Classic" AVIRIS instrument by Thorpe et al (2014) detected local enhancements of 1 ppm within a kilometer-thick atmospheric model layer. Later studies by Thorpe et al (2015) using AVIRIS-NG found similar enhancements in the distal regions of plumes associated with CH 4 fluxes of 14.2 m 3 h −1 (500 standard cubic feet per hour, scfh) under moderate (5 m s −1 ) winds. Resolving plumes of this magnitude under similar conditions should be possible with a sensitivity of 1000 ppm m. Better performance would further reduce ambiguity and improve the detail of diffuse plumes.…”
Section: Tactical Imaging Spectroscopymentioning
confidence: 76%
“…Bovensmann et al (2010) did not include transport error in their analysis which may have led to overoptimistic results. With 2 × 2 km 2 pixel resolution, CarbonSat would be limited in its ability to resolve the structure of individual methane plumes since airborne mapping shows plumes to be smaller in scale even for large point sources Thorpe et al, 2016;Frankenberg et al, 2016). The 0.05 × 0.05 km 2 resolution of GHGSat, with imaging over a 12 × 12 km 2 grid, has better potential for resolving the plume structure.…”
Section: Observing Requirements For Regional and Point Sourcesmentioning
confidence: 99%
“…The methane airborne mapper (MAMAP) retrieves methane in the SWIR at 1.6 µm, similar to SCIAMACHY, but currently lacks imaging capabilities. Imaging spectrometers initially designed for surface remote sensing have been shown to detect methane plumes with horizontal resolution as fine as 1 m either in the SWIR using the strong 2.3 µm band (Roberts et al, 2010;Thorpe et al, 2016) or in the TIR (Tratt et al, 2014;Hulley et al, 2016). These imaging spectrometers such as AVIRIS-NG (SWIR) and MAKO or HyTES (TIR) have much coarser spectral resolution than MAMAP or current satellite instruments (e.g., 5 nm for AVIRIS-NG).…”
Section: Observing Requirements For Regional and Point Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVIRIS-C sensor images spectral radiance in 224 bands from 370 nm (visible) to 2500 nm (shortwave infrared, SWIR) with 10 nm sampling and SNR of >1000:1 at 600 nm and >400:1 at 2200 nm [28,29]. There were twelve, ~12 km swath flight runs per season that provided 20% image overlap among runs.…”
Section: Simulated Hyspiri Imagerymentioning
confidence: 99%